PERENCANAAN PERBAIKAN RUANG FAKULTAS TEKNIKDI LANTAI 7 KAMPUS UNIVERSITAS MPU TANTULAR - Edison Hatoguan Manurung; Siti Wardiningsih; Pahal Sinambela; Franka Hendra Sukma; Berlin P Sitorus; Retno Indriyati Kusuma Wardani; Rudy Ady Santosa; Maher Aziz; Erik Kurniawan; Kevin Ganda Surya; Mukhamad Shodiq Sulung; Boy Sihite; Dedy Saputra Purba; Hagit Putra; Abdul Gopur; Didi Septiawan; Dodi Hadi Pamtoro; Reza Nazar Arifin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Mpu Tantular University Jakarta (UMT) is a private university located in Cipinang Besar, East Jakarta, DKI Jakarta, under the coordination of the Higher Education Service Institution (LLDIKTI) Region III. UMT operates under the Murni Education Foundation (YPBM). The Community Service Program (KKN) is a compulsory course that must be taken by students as one of the requirements for completing undergraduate studies, particularly in the Civil Engineering and Architecture Study Programs at Mpu Tantular University Jakarta. The implementation of the KKN includes planning and renovation activities for lecturers’ and department head offices. One of the activities carried out involves creating several conceptual drawings, including the layout design for the head of the department’s office, planning and design improvements for the seventh-floor room, and rendering of the proposed design.